The Effect of Recycled Media-Based Storytelling Methods on Listening Skills of Group B Children of Pah Tsung Kindergarten - Hilmi, Hilmi; Puridawaty, Brigita (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This study was conducted to determine the influence of storytelling methods on the listening skills of group B children of Pah Tsung Kindergarten. The type of research used is quantitative research with a Pre-Experimental approach using One Group Pretest-Posttest design. This study used a sample of 10 group B children. The instrument used is an observation sheet. Data collection techniques in this study used observation and documentation techniques while data analysis in this study used SPSS 20. Based on the results of the study, it was shown that there was an influence of the storytelling method on the listening skills of group B children of Pah Tsung Kindergarten. This can be seen after treatment to children three times, children can listen attentively, interpret, and can understand meaning. In addition, it is evident from the results of the analysis of the Statistical Paired Sample Test test with a sig value (2-tailed) result of 0.002<0.05 which means that Ho's hypothesis is rejected and H1 is accepted. So it can be concluded that there is an influence of storytelling methods on the listening skills of group B children of Pah Tsung Kindergarten.